Effect of Phase Relations on Speckle Pattern: Simulation and Measurement - Linlu He; Haitao Zhang; Decai Deng; Qihang Gong; Jiaqi Zu; Kuo Meng (IEEE Photonics Journal, 2019)
Speckle is an important phenomenon in various applications. It can be quantified by speckle contrast. However, at present, the influence of the phase relations among the various wavelengths on speckle contrast is rarely analyzed theoretically. Herein, a thorough method for numerically simulating the speckle pattern is presented to considering the impact of relative phase relations among wavelengths on speckle contrast. This method contains spectral shape, spectral width, and phase relations. In addition, a superluminescent pulse amplifier (SPA) with 6.5-nm bandwidth and a mode-locked laser (MLL) with 21-nm bandwidth are established to conduct the verification experiment. The experimental results show that the SPA light attains lower speckle contrast even with a narrower bandwidth than the MLL light. It is manifested that relative phase relations among wavelengths has significant effect on speckle contrast, and chaotic phase relations could be more advantageous for reducing speckle than just a broad spectrum. The simulation results agree well with experimental results. Therefore, this thorough method could provide a reliable approach to describe the characteristics of speckle pattern caused by broadband light carrying phase information. Considering the speckle contrast is positively proportional to optical coherence, this method could also be used to analyze the coherence of partially coherent light.